PENYULUHAN PROSES PASCA PANEN PALA KEPADA PETANI PALA DI DESA HILA KECAMATAN LEITIMUR SELATAN, KABUPATEN MALUKU TENGAH, MALUKU - CL, Cynthia Gracia (ABDI WINA JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
This service activity for nutmeg farmers in Hila village, South Leitimur District, Central Maluku Regency aims to increase knowledge and understanding of the nutmeg postharvest process, especially regarding drying, packaging and storage. The stages of the activities carried out are FGD activities, counseling and evaluation. The results of the evaluation of the extension activities show that the community can accept and understand the material explained and will try to make it happens in the field. Some of the obstacles that are still a shared responsibility are related to the availability of nutmeg post-harvest infrastructure in order to obtain dried nutmeg and mace according to export standards. Keywords: counseling, nutmeg farmers, postharvest nutmeg